Analisis Dimensi Life Skills Dalam Pembinaan Olahraga Bulutangkis - Fikri Nashrullah Pratama, Muhammad Satria; Yudiana, Yunyun; Hambali, Burhan; Rohmah, Oom (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to analyze the dimensions of life skills in coaching badminton in various badminton clubs. The descriptive method was used in this study involving 49 badminton athletes at clubs in the city of Bandung, with the age range of participants between 10-13 years. The instrument used in this study uses the Life Skills Scale for Sport (LSSS) instrument model developed by Cronin & Ellen which measures eight dimensions of life skills with 47 rating scale items. The data obtained were analyzed using descriptive statistics and regression using SPSS software version 29.0. The results of the analysis show that the level of athlete's life skills is in two categories, namely medium and high. Whereas in the regression analysis there is influence because it has a p value of 0.001, it also has a correlation/relationship between the eight dimensions and the overall total. This shows that these eight dimensions have an influence and relationship with the total. Based on the findings, it can be concluded that the level of life skills that exist in athletes in the Bandung City environment are in two categories, namely medium and high, with the highest average being in the dimensions of social skills, 2) there is influence and also a high significant correlation/relationship in total with eight dimensions of life skills. Keyword: Life skills, Badminton, Social skills